Transparansi Pelayanan BKSDA Kalimantan Tengah Dalam Pemberian Surat Izin Pemeliharaan Satwa Liar Yang Di Lindungi - Santoso, Yonatan Ari (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2023)
The purpose of this research is to provide knowledge on the procedures and requirements needed to obtain a license to keep or trade wildlife. In addition, this research aims to find out how the transparent of BKSDA Central Kalimantan is in granting these licenses. The method used is a qualitative research approach. The data collected in this study consisted of two types of data, namely primary data and secondary data. Primary data is data obtained through interviews and observations of employee in BKSDA. Meanwhile, secondary data is obtained in the form of archives or other written documents that support the researcher's research. The results of the study show that it is quite transparent because the implementation is carried out using procedures that have been established in accordance with KLHK regulations. BKSDA will issue a form that can be obtained directly through the BKSDA office after receiving a proposal regarding the animal to be kept. Then, the proposal will be submitted to the Ministry of Environment and Forestry for approval or rejection.